Temperature Dependence on Domain Switching Behavior in Lead Zirconate Titanate Under Electrical Load via In Situ Neutron Diffraction - Pojprapai, S.; Simons, H.; Studer, A.; Luo, Zhenhua; Hoffman, M. (Wiley-Blackwell Publishing, Inc., 2011)
The influence of temperature on the kinetics of domain switching in lead zirconate titanate was investigated by using in situ neutron diffraction. Samples were electrically loaded to 1 kV/mm at 30°C, 125°C, and 175°C, after which the diffracted patterns in the on- and off-state were compared. The results demonstrated that the degree of domain switching increases with increased temperature. Corroboration with hysteresis measurements showed that while the coercive field decreases withincreasing temperature, the degree of saturation increased significantly. According to Merz’s model, it is therefore apparent that, due to increased switching rate at high temperature, domain switchability increases with temperature.